Preliminary study on induction motor under voltage fluctuation by using field methods - Gnaciński, P.; Hallmann, D. (Scientific Journal of Gdynia Maritime University, 2017)
The paper deals with the influence of supply voltage fluctuations on an induction cage machine. Waveforms of currents, torque and rotational speed are presented. Voltage and current spectrum are discussed. The appropriate numerical experiments were made with finite elements method. The results of calculation are shown for an induction cage motor of rated power 3 kW.